The Existence of CSR Practices in MSMEs: A Study of Traditional Fishermen - Dahlan, Lukman; Alkam, Rahayu; Effendi, Soelchan Arief (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research explores CSR practices in MSMEs, focusing on the Makacua tradition practiced by traditional fishermen in Larea-rea, Sinjai Regency, South Sulawesi. Using a qualitative method with Spradley’s ethnographic approach, the study examines how Makacua is integrated into the business activities of fishermen. The findings reveal that Makacua has been voluntarily practiced for generations as an expression of religious devotion and cultural preservation. The costs of Makacua are reflected in economic, social, environmental, and religious activities, not based on profit, but on available resources. Despite its significance, Makacua remains a private practice, rarely disclosed due to cultural taboos. This research challenges the assumption that CSR is only applicable to large, financially stable entities, demonstrating that CSR can be effectively practiced even in small-scale businesses with limited resources. The study’s implications suggest that policymakers and CSR authorities should broaden their recognition of local CSR models, particularly in the MSME sector, to include practices like Makacua. Such models, grounded in social and spiritual values, could enhance CSR participation in grassroots and informal economic settings, which are often overlooked in formal CSR discussions.